CURRENT RUSSIAN EDUCATION SYSTEM MODERNIZATION PROBLEMS - E. A. Zhukov; B. F. Zaitsev (Модернизация, инновация, развитие)
Modernization process currently underway in economics of the Russian Federation subjects reveal serious discrepancy between present professional education systems and demands of regional economics real sectors in professionals of all categories from workers of leading occupations to engineers and technicians. The problem of preparation of professionals qualified in conformity with up-to-date regional economics modernization demands may be solved only through creationof equal conditions for citizens of all regions of the Russian Federation to obtain qualified professional education.